Parallelized STED fluorescence nanoscopy - Bingen, Pit; Reuss, Matthias; Engelhardt, Johann; Hell, Stefan (Optics express, 2011)
We introduce a parallelized STED microscope featuring m = 4 pairs of scanning excitation and STED beams, providing m-fold increased imaging speed of a given sample area, while maintaining basically all of the advantages of single beam scanning. Requiring only a single laser source and fiber input, the setup is inherently aligned both spatially and temporally. Given enough laser power, the design is readily scalable to higher degrees of parallelization m.